Konstruksi Identitas Niqabis melalui Selfie Instagram - Diana Safinda Asran; Wening Udasmoro (Universitas Gadjah Mada, 2020)
The media has long been used by certain religious communities to introduce their culture in society. Like the veiled Muslim group on Instagram which is called the niqabis. Automatically the existence of the niqabis is getting closer to society and is reaping significant popularity. Now the niqab is not only an attribute of religion, but also as part of an identity to a commodity of political economy. In this research, we will study further how niqabis use posts, especially selfies to construct their identity through Instagram, as done by @diananurliana and @wardahmaulina_. Diana Nurliana and Wardah Maulina are influencers and have consistently built their identity as niqabis. The analysis carried out on the two accounts shows that identity is formed through selfies with information. Both Diana and Wardah take advantage of eye gaze, frame size to corner to be prepared with the viewer. While the caption is used to provide information on photos and also as a space for expression and opinion. On the other hand, what is uploaded also aims to form subjectivity to create branding. Keywords: Identity; Instagram; Niqab; Niqabis; Selfie.